2023
DOI: 10.1039/d2ob02221d
|View full text |Cite|
|
Sign up to set email alerts
|

π-Facial selectivity in the Diels–Alder reaction of glucosamine-based chiral furans and maleimides

Abstract: Furans derived from carbohydrate feedstocks are a versatile class of bio-renewable building blocks and have been used extensively to access 7-oxanorbornenes via Diels-Alder reactions. Due to their substitution patterns these...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Next, we tried the reaction with the less reactive dienophile ethyl acrylate, which was initially unsuccessful. Based on our experience with Di-HAF , 27 we assumed that the Diels–Alder reaction with ethyl acrylate was reversible and the retro reaction dominated. Reversibility in Diels–Alder reactions with furans is a common phenomenon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we tried the reaction with the less reactive dienophile ethyl acrylate, which was initially unsuccessful. Based on our experience with Di-HAF , 27 we assumed that the Diels–Alder reaction with ethyl acrylate was reversible and the retro reaction dominated. Reversibility in Diels–Alder reactions with furans is a common phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 From this amino-sugar the platform chemicals dihydroxyethyl acetamidofuran ( Di-HAF ) 18 and 3-acetamido-5-acetylfuran ( 3A5AF ) 19–21 can be accessed through a dehydration process. These furans exhibit a rich reactivity profile 22,23 and have been employed in rearrangement reactions, 24,25 cyclo-additions 26,27 and as synthetic building blocks for the preparation of various alkaloids. 28,29…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Recently, the first studies were published demonstrating DA cycloaddition with NAG-derived nitrogen-containing furans. Chirality transfer from enantiopure Di-HAF by stereocenterinduced π-facial selectivity was reported by Minnaard et al 20 The group of Gomes 21 used 3A5AF and N-[5-(1-hydroxyethyl)-3-furanyl]acetamide (HEFA) as dienes and focused on expanding the scope of DA cycloadditions of 3A5AF with several dienophiles. The focus of this seminal report was on achieving improved yields and determining the scope of the reaction and the formation of the hydration side product.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We recently demonstrated that the inherent chirality present in chitin can be transferred to the natural product epi-leptosphaerin A via the chiral pool di-HAF platform [22]. Other research groups have shown that 3A5AF (and derivatives) [23,24] and di-HAF [25] can serve as dienes in the Diels-Alder reaction, while 3A5F has shown significant promise as a platform chemical, including as a bioconjugation handle for N-cysteine's modification [13].…”
Section: Introductionmentioning
confidence: 99%